Indoor Environmental Quality in Low Energy Buildings. (November 2015) - Fabbri, Kristian; Tronchin, Lamberto
Abstract: The Directives 2002/91/CE and 2010/31/UE greatly evolved the building and real-estate sector towards low energy building, both in the case of building retrofitting and new buildings. Thanks to the Energy Performance Certificate influence on the real estate market, or thanks to the economic crisis, as it is some new buildings - the best - were built with Energy Class A or Nearly Zero classification. The Energy Building Performance standards, e.g. CEN Umbrella and their transposition, will be improved in the future, in spite of this these should be considered solid, and designers, architects and engineers must apply technical strategies (e.g. high insulation, reduction of air leakage, use of renewable systems) in order to reduce building energy consumption. The new challenge will be to improve relations between Building Energy Performance and Indoor Environmental Quality (IEQ). As regards these relations, the CEN Umbrella provides to implement the Standard 15251. In the present paper we describe the results of IEQ monitoring in a low energy performance building (Class A+ less than 25 kWh/m 2 year). The results show that low energy performance building do not always guarantee a better category of IEQ, especially during the summer.